Hydrotreating of Sunan Candlenut (Reutealis trisperma Airy Shaw) Oil by Using NiMo-γAl2O3 as Renewable Energy - Daliya Indra Setiawan; Tun Tedja Irawadi; Zainal Alim Mas’ud (Indonesian Journal of Chemistry, 2019)
Hydrotreating process of Sunan candlenut oil by using NiMo-γAl2O3 catalyst has been successfully investigated. Preparation of NiMo-γAl2O3 catalyst by using dipping impregnation method generated catalyst used for hydrotreating process. This method consists of three stages: support activation, impregnation, and calcination. This factors influencing the process including temperature, pressure, and the ratio of Sunan candlenut oil to the H2 gas factor were examined. The hydrotreating product of fuel similar to oil was obtained at a minimum temperature of 380 °C, a pressure of 30–60 bar, and the ratio of the sample to H2 gas of 0.5–1. The diesel fuel from physical properties range for the density of 0.82–0.86 g/cm3, and kinematic viscosity of 2–6 cSt have been fulfilled by hydrotreating result. Gasoline, naphtha, diesel oil, and gas oil products of Sunan candlenut oil were obtained by distillation from hydrotreating process. Sunan candlenut oil fuel qualified fuel requirement.